Chiral Recognition and Separation by Chirality‐Enriched Metal–Organic Frameworks. Issue 28 (12th June 2018) - Das, Saikat; Xu, Shixian; Ben, Teng; Qiu, Shilun
Abstract: Endowed with chiral channels and pores, chiral metal–organic frameworks (MOFs) are highly useful; however, their synthesis remains a challenge given that most chiral building blocks are expensive. Although MOFs with induced chirality have been reported to avoid this shortcoming, no study providing evidence for the ee  value of such MOFs has yet been reported. We herein describe the first study on the efficiency of chiral induction in MOFs using inexpensive achiral building blocks and fully recoverable chiral dopants to control the handedness of racemic MOFs. This method yielded chirality‐enriched MOFs with accessible pores. The ability of the materials to form host–guest complexes was probed with enantiomers of varying size and coordination and in solvents with varying polarity. Furthermore, mixed‐matrix membranes (MMMs) composed of chirality‐enriched MOF particles dispersed in a polymer matrix demonstrated a new route for chiral separation. Abstract : Breaking the chirality bias : Inexpensive achiral building blocks and recoverable chiral dopants were used to synthesize chirality‐enriched MOFs (CE‐MOFs). The formation of host–guest complexes between the CE‐MOFs and alcohol enantiomers depended on size, coordination mode, and solvent polarity. Enantiomers could also be separated by mixed‐matrix membranes composed of CE‐MOF particles dispersed in a polymer matrix (see picture).